Pesantren dalam Bayang-Bayang Hegemoni Media: Analisis Kritis atas Framing Tayangan Xpose Uncensored di Trans7 terhadap Pondok Pesantren Lirboyo - Ade Iim; Ahmad Fauzi Zainal Abidin; Ahmad Sarbini; Asep Iwan (ALAMTARA, 2025)
This study analyzes the representation of Pondok Pesantren Lirboyo in the Xpose Uncensored broadcast on Trans7, which sparked controversy among the public and religious institutions. Using framing analysis and the theory of hegemony, this research aims to explore how the media frames pesantren as an object of spectacle and the values produced through such representations. The results show that the broadcast depicted pesantren from a negative and sensationalist perspective, highlighting certain aspects of the life of santri considered unusual. Moreover, the media framing created a dichotomy between "modernity" and "pesantren tradition," implicitly undermining the spiritual values within pesantren. The reactions to this broadcast reflect the resistance of the pesantren community, criticizing and responding to the media framing through various channels, including boycott campaigns and legal interventions. This study contributes to understanding the power dynamics in the representation of religion in mass media and the importance of media literacy and broadcast regulations that are more sensitive to diversity. The practical implications of this research include the need to strengthen regulations that protect religious institutions from media exploitation